Instrumentasi Pemantauan Perairan Berbasis Telemetri Pada Prototipe Unmanned Surface Vehicle (USV) - Dananjaya Ariateja; Uvi Desi Fatmawati; Iqbal Ahmad Dahlan (Universitas Negeri Padang, 2021)
Technological advances, especially in the field of remote control, both automatic and non-automatic, are very rapid. This can be seen from the technological capabilities that can work on the land, air, and water. Indonesia as one of the largest archipelagic countries in the world that have borders such as land, air, and vast seas must have this technology to anticipate the potential for problems that endanger citizens and the state. So far, Indonesia has reached this technology, for example, drone technology as a border monitoring mission through the air and aerial photography purposes. Ground robots are used to defuse remote-controlled bombs. To complete this, the researchers conducted research related to a remotely controlled prototype of an unmanned water vehicle. The research conducted discusses the manufacture of prototypes of unmanned surface vehicles and control stations that can communicate with each other. This prototype is controlled by the Arduino Nano microcontroller module, while the main control system uses a desktop-based application that is run via a laptop. Based on the test results, sending sensor data to Arduino and to the control station via the RF-module media went well. The transmission distance of transmitting sensor data and navigation control reaches approximately 250 meters, while the transmission distance of IP camera images reaches approximately 9 meters.